Creative Digital Literacy in Reducing War Flaming on Social Media - Arisanty, Melisa; Riady, Yasir; Amellia Kharis, Selly Anastassia; Sukatmi, Sri; Zubir, Edward; Ajmal, Muhammad (Communicatus: Jurnal Ilmu komunikasi, 2024)
War flaming constitutes one of the perilous practices prevalent on social media platforms. This might result in discomfort associated with social media usage, leading to melancholy, anxiety, excessive worry, and disturbances in mental health. War Flaming has become a prominent issue that necessitates enhancing digital literacy on social media platforms. This study employed a qualitative methodology, with data collected through observation, in-depth interviews, and Focus Group Discussions (FGD). Informants were selected using standard case sampling. The selected informants include the Directorate of IKP from the Ministry of Communication and Information of the Republic of Indonesia, SiBerkreasi, digital technology and culture experts, and specialists in social campaigns. The findings indicated that digital literacy building aimed at mitigating war flaming on social media involved creating innovative social campaigns through pertinent language and a human-centric literacy approach. This strategy seeks to engage Generation Z, empowering youth communities as proactive advocates against hoax narratives on social media. It emphasizes collaboration among governmental entities, community leaders, and journalists within the anti-war flaming educational initiative, alongside the optimization of TikTok and Instagram for disseminating positive content, and partnerships with young influencers to promote the significance of digital reputation. Creative digital literacy, facilitated by social campaigns and multisectoral cooperation, effectively mitigates war flaming on social media, enhances Gen Z awareness, and promotes mental health through affirmative material.